SOCIAL, PSYCHOLOGICAL AND BEHAVIOURAL DATA ANALYSIS - Christopher, G.; P, Dinesh; Karthikeyan, J.; James, Justin (International Journal of Psychosocial Rehabilitation, 2020)
In the growing world research demand and importance of data analysis in the current scenario have generated many eye openings worldwide. Statistics are a major role in all aspects of our daily life. Statistics are a major role in all aspects of our daily life. Most very familiar statistical methods are hypothesis testing, regression and variance analyses estimated through the statistic tools like SPSS, SAS, and R programming and STAT. These are the basic tools concentrate for every research in data analysing. Statistical estimations are complicated while hosting the new way of methods and procedure for the assumption. So the scientists help them to solve their problem and prove their view of data analysing into the statistical influence within the mathematical calculation. In the statistical analysis, mathematics can be hiding behind statistics. This wide range of statistics can help the researcher to make their deliverance perfectly. In social science, the research used varies statistical tools and methods but compare to others statistical tool SPSS will posses major role in social science research especially in English language Teaching. This research paper title aimed to reveals in statistics brought great bear in an art of shaping data analysis in an English language teaching. Statistic methods are a wide range of process which helps to analyse data in various aspects. The accurate calculation and analyses of mean variables regression and test comparisons and another way of statistical techniques are major components of English language teaching. The main aim of this research to know about the use of the SPSS statistic tool in language teaching and it can also use to analysing data accurately.